THE RELATIONSHIP OF LOW BIRTH WEIGHT (LBW) WITH DEATH NEONATAL IN INDONESIA (2017 IDHS DATA ANALYSIS) - Rostina, Rostina; Arlianti, Nopa; Abdullah, Asnawi (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2022)
Background: Neonatal mortality is a reflection of a country's health status and until now, health development is still an important government program. The purpose of this study was to determine the relationship between Low Birth Weight (LBW) and neonatal mortality in Indonesia after confounding factors (education, household wealth index, age, smoking, parity, birth spacing, antenatal visits and history of abortion) were controlled and to determine the size of Population Attributable Risk of LBW to neonatal mortality in Indonesia. Indonesia 2017. Methods: The design of this research was cross-sectional with multivariate logistic regression analysis using secondary data from the 2017 IDHS. The sample in this study were women who had been married and gave birth to live babies from 2012-2017 as many as 16.343 samples. Results: The study showed that there is a relationship between LBW and neonatal mortality (OR=6.79, 95% CI=4.98-9.26, p value=0.000). Then the dominant factor that is most related to neonatal mortality is LBW with a p value of 0.000 and parity with a p value of 0.005. Conclusion: In order to reduce neonatal mortality, it is hoped that the government and the society can play an active role in reducing and controlling LBW by increasing antenatal care. As well as encouraging pregnant women to check their pregnancies and deliveries by skilled health workers.